Chladni Figures Revisited based on Nanomechanics - HEGNER, MARTIN (My University, 2007)
Chladni patterns based on nanomechanics in the microfluidic environment are presented. In contrast with the macroscopic observations in the gaseous environment, nanoparticles are found to move to the nodes, whereas micron-sized particles move to the antinodes of the vibrating interface. This opens the door to size-based sorting of particles in microfluidic systems, and to highly parallel and controlled assembly of biosensors and nanoelectronic circuits.
PUBLISHED
Keywords: Physics